Application synchronisation on public displays based on PubSubHubbub - Pereira, Manuel Frederico da Costa Dias (2013)
Large-scale pervasive public displays networks are becoming an emerging paradigm and represent a radical transformation in the way we think about information dissemination in public spaces. One of the features of pervasive public display systems is their ability to create experiences that span across multiple displays in a coordinated fashion. Proprietary single site display solutions exist but these are not open to third-party developers. On the other hand, scalable open systems that enable large-scale, synchronised and multi-screen experiences, spanning multiple networks domains will call for the definition of multiple administrative boundaries that accommodate function partitioning. In our research, we are studying the key requirements involved in this open application synchronisation and present our initial work on designing a synchronisation model and Application Programming Interface for public displays application developers that is built on top of the PubSubHubbub protocol, an open protocol for distributed publish/subscribe communication on the Internet.